PERAN MATA KULIAH PSIKOLOGI KELUARGA DALAM MEMBANGUN KESIAPAN MENIKAH MAHASISWA STDIIS JEMBER - Ari Widodo; Khoirul Ahsan (USRAH: Jurnal Hukum Keluarga Islam, 2025)
Marriage is a noble act of worship; therefore, it requires thorough preparation before it is undertaken. One way to prepare for marriage is by studying family psychology. Family psychology is a field that explores the mental and emotional aspects within the family unit. Sekolah Tinggi Dirasat Islamiyah Imam Syafi’i (STDIIS) is a private Islamic higher education institution located in Jember Regency, East Java. The Family Psychology course is one of the core courses offered in the academic program at STDIIS Jember.This study aims to examine the role of the Family Psychology course in preparing students for marriage. A qualitative research method with a case study approach was used in this study. The results indicate the following; 1. The family psychology course plays a role in two main areas: (a) Emotional and mental readiness, and (b) Cognitive and attitudinal preparedness. 2. There are two aspects that play a role in the Family Psychology course: (a) Personality and motivation, and (b) Communication patterns and conflict management. 3. STDIIS students perceive the Family Psychology course as having an important role in preparing them for marriage, with course materials that are highly relevant and appropriate.